2002
DOI: 10.1051/rnd:2002013
|View full text |Cite
|
Sign up to set email alerts
|

Potential uses of milk epithelial cells: a review

Abstract: -Secretions collected from the mammary gland of different species contain heterogeneous populations of cells including lymphocytes, neutrophils, macrophages and epithelial cells in different species. Several factors influence the somatic cell count in milk and the distribution of cell types, such as species, infection status, physiological status and management practices. The epithelial cells are shed into milk during the lactation process. Most of them are viable and exhibit the characteristics of fully diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 57 publications
3
117
0
4
Order By: Relevance
“…It was identified that human breast milk possesses specific CAM such as CD 166, CD 31, CD 49d, CD 54, but lack CD 106. In addition, human breast milk was also identified to possess lymphocytes, monocytes and macrophages, which is coherent with earlier reports (Hamosh 2001;Boutinaud and Jammes 2002;Pabst 1997;Hanson 1999). Furthermore, the existence of CD 105 and CD 31 revealed the presence of endothelial progenitor cells and endothelial cells in breast milk, enhancing the property of transendothelial migration.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It was identified that human breast milk possesses specific CAM such as CD 166, CD 31, CD 49d, CD 54, but lack CD 106. In addition, human breast milk was also identified to possess lymphocytes, monocytes and macrophages, which is coherent with earlier reports (Hamosh 2001;Boutinaud and Jammes 2002;Pabst 1997;Hanson 1999). Furthermore, the existence of CD 105 and CD 31 revealed the presence of endothelial progenitor cells and endothelial cells in breast milk, enhancing the property of transendothelial migration.…”
Section: Discussionsupporting
confidence: 89%
“…The self renewing multipotent mammary stem cell has been extensively studied as a prognostic tool for breast cancer (Stingl et al 2001;Dontu et al 2003). Breast milk, being the secretary product of the mammary gland in the postpartum period is a complex mixture of interacting compounds like proteins, antibodies, vitamins, growth factors, hormones, cytokines and several immune factors for the newborn (Hamosh 2001;Boutinaud and Jammes 2002;Hanson et al 2001;Pabst 1997;Hanson 1999). Accumulating evidences suggests that breast milk encompasses epithelial cells, colostral corpuscles, polymorphonuclear leukocytes, mononuclear phagocytes and lymphocytes, with those of epithelial lineage forming the main bulk of cells within 2 weeks of establishing lactation (Fan et al 2010;Hanson et al 2001;Labbok et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In advancing our recent observation that bovine Hp mRNA is present in tissue homogenates from different parts of the mammary gland (Hiss et al, 2004), we could herein assign leukocytes as one cellular source of mammary Hp mRNA expression. Since milk somatic cells generally comprise about 90% blood-derived cells (Boutinaud and Jammes, 2002), the blood derived cells may contribute towards the Hp mRNA detected amongst the somatic cells in this study. However, our results could not clarify whether stromal or parenchymal cells of the mammary gland itself are capable of Hp mRNA synthesis.…”
Section: Resultsmentioning
confidence: 93%
“…Além das células do sistema imune, também são encontradas no leite células epiteliais relacionadas ao término da vida secretória e provenientes da descamação do tecido alveolar, presença que sugere a eliminação de células "mortas" (Boutinaud;Jammes, 2002), que variam de forma crescente do começo para o fim da lactação (Pereira et al, 2001;Coldebella et al, 2004). Neste contexto, a contagem de células somáticas no leite é um indicador da evolução e saúde da glândula mamária (Burvenich et al, 1994;Paape et al, 2002), já que, em uma glândula mamária infectada, mais de 90% das células somáticas encontradas no leite serão neutrófilos (PMN) (Boulanger et al, 2001).…”
Section: Introductionunclassified